Pemanfaatan Chlorella Sp. Dengan Penambahan Kombinasi Fe Dan Co Untuk Menyisihkan Nitrogen Total Pada Limbah Cair Sawit Menggunakan Flat-Photobioreactor - Indah Kartika Zulfa; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Palm oil mill effluent containing pollutants and has high content of organic matter. Organic material contained in palm oil mill effluent can be used as nutrition by microalgae Chlorella sp. and can reduce Total Nitrogen content in palm oil mill effluent. The nitrogen total removal process was carried out in a flat-photobioreactor with various concentrations of combinade Fe dan Co in the amount Fe is 0,3; 0,5; and 0,7 mg/L and Co is 1 and 2 mg/L with contact times of 0, 1, 3, 5, and 7 days. The results showed that at a combination of 0,5 mg/L Fe + 0,2 mg/L Co, the highest microalgae cell growth was 6,00 x 106 cell/ml and the highest removal efficiency of organic matter of total nitrogen is 85,3%. Keywords: Chlorella sp., Fe (Iron), Co (Cobalt), Total Nitrogen, flat-photobioreactor